Maternal Exposure to Air Pollution and Its effects on Neonatal Health: A Review - Chauhan, Kavita; Singal, Kabir; Agarwal, Anshoo; Syed, Asmara; Chatha, Wajid Ali; Hussain Shah, Syed Sajid; Kauser, Fariha; Subramaniam, S. Geetha (Journal of Neonatal Surgery, 2025)
Background: Air pollution has emerged as an important cause of neonatal morbidity around the globe. Fetal development is affected by the exposure of air pollution to the expecting mothers, particularly in the initial months when the organogenesis is in process. Material and methods: After the searching the common databases such as PubMed, Google scholar, Scopus and web of science, a list of the research articles were shortlisted. The key words used to search the research papers included ‘ air pollution, particulate matter, ozone, SO2, CO, NO2 , lead, hydrocarbons, neonatal abnormalities, congenital heart diseases, limb anomalies, neural tube defects, pregnancy and early gestation.’ Results: A total of sixty-one research papers were collected and compiled. Significant number of research articles documented the relation of air pollution with the development of congenital diseases among neonates. The important new born diseases associated with the air pollution include heart defects, orofacial defects, neural tube defects, polydactyly and syndactyly. Discussion: The congenital heart diseases of the newborn are most common ailments which are associated with intrauterine high exposure of particulate matter, SO2, CO, NO2 & O3. The increased normalized difference vegetation index (NDVI) of the permanent residence of the mothers reduces the possibility of congenital heart diseases among the neonates. Conclusion: Air pollution is contributing in the morbidity and mortality of the neonates. The control of air pollution is of vital importance for these preventable neonatal diseases by adapting suitable measures such as increasing the tree plantation and reducing the emission from vehicles, industries, household burning and wildfires.